Uji Aktivitas Antioksidan Kombinasi Ekstrak Buah Tomat (Solanum Lycopersicum L.) Dan Buah Pepaya (Carica Papaya L.) Menggunakan Metode DPPH - Vicko Suswidiantoro; Novi Ana Nurlaili; Indah Safitri; Amanda Tirtasena; Kiki Ariska; Mela Annisa; Mela Kurniasari; Wina Safutri; Riza Dwiningrum (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Free radicals are unstable molecules that can cause cell damage and trigger various degenerative diseases. One effort to inhibit the adverse effects of free radicals is to use antioxidants. Tomato fruit (Solanum lycopersicum L.) and papaya fruit (Carica papaya L.) are known to contain various antioxidant compounds such as lycopene, vitamin C, flavonoids, and phenolics. The purpose of this study was to determine the antioxidant activity of a combination of tomato and papaya fruit extracts using DPPH (2,2-diphenyl-1-picrylhydrazyl) method and determine the best value of IC₅₀ from three comparisons of extract combinations. This type of research is a qualitative and quantitative experimental study. Tomato and papaya fruits were extracted using maceration method with 96% ethanol. The result of this study was that in three comparisons the combination of tomato and papaya extracts, 25%:75%, 50%:50%, and 75%: 25% based on IC50 parameters showed very strong antioxidant activity. The ratio of 25%: 75% resulted in the value of IC50 of 2.44 ° 0.003 ppm, the ratio of 50%: 50% of 2.14 ° 0 ppm, and the ratio of 75%: 25% of 2.4710 ° 0.003 ppm. The conclusion of this study is that in the statistical test comparison of the combination of tomato and papaya extracts, the three comparisons have a very strong antioxidant activity and there is no significant difference, with a significance value of p = 1,000.